The Effect of Ta'zir Goals on the Rules of Plurality of Crimes - morad abasi; Mohammad Hadi Sadeghi; Fazlollah Foroghi; Seyed Mohamad Mahdi Sadati (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2022)
plurality of crime is a special situation in which a person has committed several crimes before a final conviction, and Lawyers have expressed different views on the rules of plurality of crime. the regulation of criminal institutions cannot be independent of the goals of the criminal response. The present article is a descriptive-analytical study using documentary sources. This study answers the question of how the plurality of crime is affected by the goals of ta'zir and creates a new rule? Since the main goal in ta'zir is correction, and in addition to correction, compensation for the damage is also considered. Criminal talent should also be considered in the process of correction.it is also necessary to pay attention to criminal motives. Therefore, in committing crimes, if the motives are similar, they will interfere and will be limited to just one ta'zir. And if the motives are dissimilar, any motive independent of the other motive is the subject of ta'zir, and the plurality of motives will cause the plurality of ta'zir reactions. Unless the goal is achieved by applying an appropriate ta'zir,in which case the causes will interfere.In cases where the purpose of ta'zir is compensation, the plurality of victims will lead to the plurality of ta'zir,even if the motive is the same.in order to provide the Victims' interests, a reaction must be adopted in the light of which the perpetrator's correction is also achieved.